Books and social media how the digital age is shaping the printed word - Johnson, Miriam J. (Milton Park, Abington, Oxon ; New York, NY : Routledge, 2021)
Social media and digital technologies are transforming what and how we read. Books and Social Media considers the way in which readers and writers come together in digital communities to discover and create new works of fiction. This new way of engaging with fiction stretches the boundaries of what has been considered a book in the past by moving beyond the physical or even digitally bound object to the consideration of content, containers, and the ability to share. Using empirical data and up-to-date research methods, Miriam Johnson introduces the ways in which digitally social platforms give rise to a new type of citizen author who chooses to sidestep the industry's gatekeepers and share their works directly with interested readers on social platforms. Gender and genre, especially, play a key role in developing the communities in which these authors write. The use of surveys, interviews, and data mining brings to the fore issues of gender, genre, community, and power, which highlight the push and pull between these writers and the industry. Questioning what we always thought we knew about what makes a book and traditional publishing channels, this book will be of interest to anyone studying or researching publishing, book history, print cultures, and digital and contemporary literatures.
Keywords: Books and reading -- Technological innovations; Publishers and publishing -- Technological innovations; Social media -- Authorship; Fiction -- Publishing; Electronic publishing; Self-publishing.; LITERARY CRITICISM / General